2012
DOI: 10.1093/cercor/bhs113
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of Gyral Folding and Structural Connection Patterns in Primate Brains

Abstract: Both cortical folding and structural connection patterns are more elaborated during the evolution of primate neocortex. For instance, cortical gyral shapes and structural connection patterns in humans are more complex and variable than those in chimpanzees and macaques. However, the intrinsic relationship between gyral folding and structural connection and their coevolution patterns across primates remain unclear. Here, our qualitative and quantitative analyses of in vivo diffusion tensor imaging (DTI) and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 29 publications
19
86
0
Order By: Relevance
“…The results from both approaches led to the disconcerting conclusion that only a relatively small proportion of the cerebral cortex is able exchange any track lines with the deep white matter. In general, in agreement with previous observations (36)(37)(38), seeding was more successful on gyral crowns than in sulci. Our findings suggest that this bias results in large measure from the challenges for tractography posed by superficial white matter systems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results from both approaches led to the disconcerting conclusion that only a relatively small proportion of the cerebral cortex is able exchange any track lines with the deep white matter. In general, in agreement with previous observations (36)(37)(38), seeding was more successful on gyral crowns than in sulci. Our findings suggest that this bias results in large measure from the challenges for tractography posed by superficial white matter systems.…”
Section: Discussionsupporting
confidence: 92%
“…We focused on intrinsic white matter features in the vicinity of the WGB and their impact on the accurate detection of long-range cortical connections. We first demonstrate that, in agreement with previous findings (36)(37)(38), tractography methods are biased in their identification of long-range projections toward cortical gyri. Based on detailed examination of both the dMRI data and accompanying histological sections, we next determine that much of this bias can be ascribed to the challenges associated with the complex arrangement of superficial white matter fiber systems commonly known as "local association fibers" (39,40).…”
supporting
confidence: 84%
“…Not only is increased gyrification useful for fitting more neurons within the skull, but patterns of sulci and gyri have direct implications with regard to the neural network (Ventura-Antunes et al 2013). As would be expected from a trait that is at least partially controlled by genetic variation, sulci are not randomly distributed across the cortex; consistent folds appear within species and the degree and pattern of cortical folding shows phylogenetic trends in primates (Zilles et al 1989(Zilles et al , 2013Krubitzer 2009;Chen et al 2013). There are a number of hypotheses explaining the mechanisms behind the development of cortical gyrification and why sulci appear where they do, many involving mechanical tension on axonal tracts, the neuronal connections that allow communication between brain regions.…”
mentioning
confidence: 90%
“…It also indicated that G-networks have stronger functional communication. This result offers a theoretically novel understanding of the recent literature results in [1,2] that white matter fiber connections concentrate on gyri. This organizational principle will enhance the overall efficiency and small-worldness of structural brain network on gyral regions, heighten the functional interaction on gyral regions, and suggests that gyri might be the structural and functional hubs of the cerebral cortex.…”
Section: Resultsmentioning
confidence: 56%
“…Prior literature studies [1][2][3] showed that the white matter fibers connected to gyri are significantly denser than those connected to sulci. This finding has been replicated in a range of primate brains including human, chimpanzee, and macaque monkey via diffusion tensor imaging (DTI) and high-angular resolution diffusion imaging (HARDI) [1,2], and might suggest the different roles of gyri and sulci in structural and functional brain networks. Inspired by the above finding, we hypothesize in this paper that structural and functional brain networks constructed from gyral, sulcal and cortical regions might exhibit different graph properties and functional interaction patterns that reflect the fundamental organization of the cortical architecture.…”
mentioning
confidence: 97%